2020
DOI: 10.3389/fcell.2020.576391
|View full text |Cite
|
Sign up to set email alerts
|

Recent Update of HDAC Inhibitors in Lymphoma

Abstract: Modulating epigenetic modification has been recognized for over a decade as an effective therapeutic approach to cancer and many studies of histone deacetylase (HDAC), one of the best known epigenetic modulators, have been published. HDAC modulates cell proliferation and angiogenesis and plays an essential role in cell growth. Research shows that up-regulated HDACs are present in many cancer types and synthetic or natural HDAC inhibitors have been used to silence overregulated HDACs. Inhibiting HDACs may cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 132 publications
0
59
0
Order By: Relevance
“…It has its pan-HDACi activity in common with the above-mentioned HDACi and is active at a nanomolar to low micromolar range. Belinostat displays low toxicity in patients, and side effects are mostly manageable [ 84 , 95 , 133 , 134 , 135 , 136 ]. Belinostat is potent at inhibiting cell proliferation [ 137 ] and has successfully stimulated cell lines and primary CD4 + T-cells, latently infected with HIV-1, to express virus [ 111 ] ( Table 1 ).…”
Section: Manipulation Of Histone Modificationmentioning
confidence: 99%
“…It has its pan-HDACi activity in common with the above-mentioned HDACi and is active at a nanomolar to low micromolar range. Belinostat displays low toxicity in patients, and side effects are mostly manageable [ 84 , 95 , 133 , 134 , 135 , 136 ]. Belinostat is potent at inhibiting cell proliferation [ 137 ] and has successfully stimulated cell lines and primary CD4 + T-cells, latently infected with HIV-1, to express virus [ 111 ] ( Table 1 ).…”
Section: Manipulation Of Histone Modificationmentioning
confidence: 99%
“…In addition, HDACi directly acts on tumor cells by upregulating MHC class I molecules and indirectly by eliminating myeloid-derived suppressor cells ( 35 ). Notably, HDACis can increase the expression of immune-related molecules in different cancer types ( 36 , 37 ). In our study, treatment with HDACi increased the gene expression of defined IC receptors mainly in AML BM-infiltrating CD8 + T cells and partially in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial success in T-cell lymphoma and multiple myeloma, most clinical trials for several solid cancers, including ovarian, NSCLC, colorectal and prostate, indicated that HDAC inhibitor monotherapy is not an effective treatment [ 153 , 154 , 155 , 156 ]. This could be due to poor pharmacokinetics and high toxicity profiles [ 157 ], or due to distinct genetic or epigenetic alterations present in hematological cancers [ 79 , 158 ]. Thus, future studies in solid tumors should focus on using HDACi in stratified settings, combinatorial approaches, or enhanced drug delivery methods.…”
Section: Effects Of Hdac Inhibitors and Therapeutic Implications For Tumor Heterogeneitymentioning
confidence: 99%